The Inscription of Word Gempeng and 899 as Petirtaan Jolotundo’s Cultural Identity - Fatihah, Lauhil; Riyanto, Edi Dwi (Mudra Jurnal Seni Budaya, 2025)
Petirtaan Jolotundo is one of two petirtaans (sacred bathing places) on Mount Penanggungan. It is an important archaeological heritage site, known for having the oldest recorded date in the Penanggungan Mountain area—899 Saka or 977 AD. Within the petirtaan is an inscription carved on its eastern wall, visually prominent and written in Old Javanese (Kawi) script, containing the word Gempeng and the number 899. This research aims to uncover Petirtaan Jolotundo's cultural identity through the interpretation of these two inscriptions. The study was conducted at the site of Petirtaan Jolotundo, located in Biting Hamlet, Seloliman Village, Trawas District, Mojokerto Regency, East Java Province. This qualitative research adopts a case study approach, focusing specifically on Petirtaan Jolotundo. Data collection techniques include observation, literature review, and interviews. The data analysis method follows an interpretative qualitative approach, applying Norman Fairclough's theory of critical discourse analysis, which comprises three levels: textual analysis, discursive practice, and social practice. The results of this study show that the inscriptions—Gempeng and 899—serve as cultural markers that reveal the identity of Petirtaan Jolotundo and the Old Javanese community. These inscriptions highlight the community's role in shaping and preserving the site's cultural significance across generations.